(untitled) (Research, Society and Development, 2023)
The present research had the general objective to report the experience lived as a social worker in the reception and care of people diagnosed with Autism Spectrum Disorder and their families, in a public mental health institution in the city of Óbidos-Pará. In the methodological course we used a qualitative approach, descriptive research, field research and experience report. The instruments were direct observation and the field notebook. The theoretical framework was based on public policies focused on the theme, the context of socioeconomic inequality in the country and the intervention of the social worker in public health. The research results revealed the discontinuity in the treatment of people with Autism Spectrum Disorder, family members with difficulties to exercise care, unsystematic psychosocial and intersectoral network, technical team with little knowledge on the subject and lack of training. We conclude that the user’s needs should be the central issue and the social worker needs to define the planning aimed at individual and collective care, as well as articulate with the psychosocial and intersectoral service networks, aiming to achieve satisfactory results and qualify the professional intervention.